2017
DOI: 10.1002/bmc.3931
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic profiling of seminal plasma in nonobstructive azoospermia men: A noninvasive detection of spermatogenesis

Abstract: Male factor infertility is involved in almost half of all infertile couples. Lack of the ejaculated sperm owing to testicular malfunction has been reported in 6-10% of infertile men, a condition named nonobstructive azoospermia (NOA). In this study, we investigated untargeted metabolomic profiling of the seminal plasma in NOA men using gas chromatography-mass spectrometry and advance chemometrics. In this regard, the seminal plasma fluids of 11 NOA men with TESE-negative, nine NOA men with TESE-positive and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Metabolites, products of metabolic reactions, appear in numerous biochemical pathways [ 42 ] and have been reported as potential biomarkers for male fertility [ 10 , 20 , 25 27 ]. At ejaculation, spermatozoa are suspended in the seminal plasma and it marks clear qualitative and quantitative differences in its biochemical composition [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites, products of metabolic reactions, appear in numerous biochemical pathways [ 42 ] and have been reported as potential biomarkers for male fertility [ 10 , 20 , 25 27 ]. At ejaculation, spermatozoa are suspended in the seminal plasma and it marks clear qualitative and quantitative differences in its biochemical composition [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, organic acids play crucial roles during anabolism by providing C-atom backbones [38]. Studies have previously reported the presence of organic acids in human spermatozoa [31, 32] and seminal plasma of bulls [30] and humans [27, 41, 42]. Fatty acids, in turn, are involved in the structural organization of the sperm membranes, energy metabolism, and signaling molecules [12, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Both LC and GC/MS are noninvasive techniques suitable for the discovery of molecular markers of phenotypes and physiological processes as well. In this regard, seminal plasma metabolites identified by GC/MS have been listed as potential markers of nonobstructive azoospermia in men (Gilany et al, 2017) and other studies also confirm the importance of seminal and sperm metabolites for evaluation of subfertility and infertility in humans (Davalieva et al, 2012). Comprehensive analyses of seminal plasma and sperm metabolomes from farm animals are still incipient, but recent reports have shown meaningful associations between seminal fluid metabolites and bull fertility (Kumar, Kroetsch, Blondin, & Anzar, 2015; Velho et al, 2018).…”
Section: Introductionmentioning
confidence: 90%